2020
DOI: 10.1088/1361-6668/ab89ed
|View full text |Cite
|
Sign up to set email alerts
|

Loss characteristics of HTS coated conductors in field windings of electric aircraft propulsion motors

Abstract: High-temperature superconducting (HTS) coated conductors (CCs) are widely regarded as a promising candidate to enable very high power density motors. These machines operate at high rotational speeds, with some designs going up to 12 000 rpm. HTS CCs are applied to the field windings of these motors to increase the magnetic loading and hence the power density. Even though the superconducting field windings operate with a DC current, due to the magnetic field environment, losses are present. This paper examines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This paper is a follow-up work of our previous publications [25][26][27][28]. TFSs are a potential field source applied to highspeed HTS machines.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This paper is a follow-up work of our previous publications [25][26][27][28]. TFSs are a potential field source applied to highspeed HTS machines.…”
Section: Discussionmentioning
confidence: 91%
“…For now, the electromagnetic behaviour of HTS TFSs under high-frequency fields remains unclear. In addition, according to our previous research work [25][26][27][28], at frequencies higher than 100 Hz, it is necessary to consider the multilayer physical structure of HTS CCs to quantify magnetization loss due to the skin effect. The existence of the copper stabilizers, silver overlayer, and substrate can influence the loss distribution inside CCs [29].…”
Section: Introductionmentioning
confidence: 99%
“…Also for dynamic loss, it was shown that it is mainly the perpendicular field, which contributes towards the loss [30]. Additionally, the induced loss is highly frequency dependent, a high frequency leads to higher losses [31, 32].…”
Section: Superconducting Field Windingmentioning
confidence: 99%
“…However, the unique behaviors of NI magnets affected by the dynamic resistance have not yet been clearly observed. The dynamic resistance is recognized as an important influence factor occurring in synchronous machine applications [9,17,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%